Hair grows hair: Dual-effective hair regrowth through a hair enhanced dissolvable microneedle patch cooperated with the pure yellow light irradiation. (December 2021) - Hong, Can; Zhang, Guoliang; Zhang, Wei; Liu, Jiaqi; Zhang, Jiao; Chen, Yutong; Peng, Haichuan; Cheng, Yukai; Ding, Xingwei; Xin, Hongbo; Wang, Xiaolei
Highlights: A collaborative hair regrowth concept inspired from seed germination. Hair derived nanoparticles was integrated with the exosomes of stem cells to promote hair regeneration. The homemade low-color-temperature yellow light (1900 K) facilitates hair regrowth. Abstract: Inspired by the progress of seed germination (plowing, breeding and lighting), we presented a similar collaborative hair growth technology, which integrated soluble microneedle patches (MNs) with the exosomes of human amniotic mesenchymal stem cells (hAMSCs) and hair nanoparticles (HNP). The HNP-decorated microneedle patches (HMNs) could successfully penetrate the cuticle (plowing) and assist in delivering the exosomes of hAMSCs into the dermis to excite hair follicles stem cells (breeding), allowing hair follicles to entry anagen from telogen. Meanwhile, our homemade low-color-temperature yellow light (1900 K) also alleviated the inflammation of hair follicles (lighting), thus further promoting hair regrowth. After conducting animal experiments of three kinds of models, our data demonstrated this synergistic strategy could effectively facilitate hair regrowth within 7 days compared with the conventional monotherapy. In vitro and in vivo biocompatibility studies also showed inconspicuous adverse effects or inflammation, elucidating its broad prospect for clinical application. Graphical abstract: Image, graphical abstract